Implementasi Inventory Menggunakan Sistem ERP Ginee pada Toko Online Sembilan Nine Shop - Pricilia Caroline; Lufty Abdillah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
Sembilan Nine Shop online shop is a baking material store that serves online purchases through several online merchants. Sembilan Nine Shop have many types and variants of products that for sale. In managing its inventory, the Sembilan Nine Shop online store does not yet use information technology. Currently for warehouse activities still use the method of managing and collecting inventory data in the warehouse manually. This causes the goods in the warehouse to have no categories in their storage and the stock is the difference between physical and online merchants. This is the reason for the need for an information system that can manage inventory in the Sembilan Nine Shop online store. In this study, the author uses the ERP life cycle system implementation method. It is hoped that with the implementation of the Ginee Inventory ERP system for the online store, Sembilan Nine Shop can better manage and record the goods in its warehouse.